Estudio de factibilidad para la creación de una empresa de confecciones (2012)
Through this project it is intended to demonstrate that in order to create an investment you must previously create an adequate and ordered feasible study. We begin by observing the general knowledge and definition of the product, geographical distribution of the consumer market, demand analysis, offer, commercialization and prices of the girl apparel. We found that the city of Armenia has 70% of available merchandise for girls between the ages of 4 and 12 which have not been satisfied because of the competition which allows us to see an opportunity to develop a children’s apparel company for this segment. Later, we identify a technical study where we will build the size and location of the company, availability of capital, and adequate production and commercialization. Regarding the technical and engineering aspects, we have found that the most adequate place to produce the children’s apparel because of low costs and location is the center of the city, more specifically around CAM where there are workshop branches that supply to a variety of stores. It is essential for any company to know the benefits of performing legal constitutions and regulations governing the activity that was carried out. We were able to identify from the organizational and legal study that the appropriate framework to implement within a company that is devoted to manufacturing and commercializing apparel is an organization based on the system aligned where every employee reports to his immediate employer in a way that the responsibility and authority are established so that decisions can be made easily and quickly. Also, the constitution is determined by a SAS which is designed to facilitate procedures, reduce costs and have more flexibility in the organization. Through the environmental study we were able to conclude that even though textile companies have little impact on the environment, an environmental management plan must be performed with the waste that is produced after processing the garments which can be reused for the development of other products. And finally the financial study of Solo Blusitas SAS determined that it is an impractical project since the general diagnosis about the financial situation shows that the investment recuperation is slow and would need a constant intake to maintain the market.